Pustakawan Dan Budaya Perpustakaan - Suwarno, Wiji (Pustakaloka, 2014)
Librarian  is not only a man working  to  serve users,  siting behind  desk,  but  he  also must  be  a  creative  ofcers, who  can market him self and his library. This article tries to explore how librarians can infuence his  institution with his work culture, and how people could under estimate to them and their institution.   Library and  librarians must strive  to achieve a good governance, and ethics code is a solution to this negative impression to both. Ethics code will guide librarian to act professionally, will increase a brand and an image of them